Optimal Placement of Phasor Measurement Unit (PMU) using genetic algorithm & cuckoo search algorithm - Midi, Nur Shahida; Mohd Hanfi, Nurhazwani; Hussin, Mohd Fahmi; Abu Hanifah, Mohd Shahrin (IEEE, 2025)
The usage of Phasor Measurement Units (PMUs) are becoming popular and populating the power system grids rapidly due to the need for big data in electrical power system analysis. It is a crucial component for managing, controlling and monitoring system performance by providing synchronized measurements of voltage, current and frequency in real-time. However, the expensive cost of PMUs makes it impractical to install them on every bus in the power system grid. This work investigates the use of metaheuristic algorithms to solve the Optimal PMU Placement (OPP) problem, aiming to minimize the number of PMUs required. The IEEE 57-bus test system is used as the benchmark model for algorithm evaluation. Two algorithms, Genetic Algorithm (GA) and Cuckoo Search Algorithm (CSA), are implemented and tested under normal operating conditions and with the consideration of Zero Injection Buses (ZIBs). The algorithms are assessed using key performance metrics, including the Bus Observability Index (BOI) and the System Observability Redundancy Index (SORI). Based on these evaluations, the algorithm that demonstrates higher efficiency and effectiveness is selected for further analysis.